The Impact of Exchange Rates on Macroeconomic Factors in Lao PDR from 2012-2021: https://doi.org/10.69692/SUJMRD0802216 - SIPHANTHONG, Dr. Bounthavy; CHITTAPHONE, Namfonh; SENGDARA, Chansamone; KEODUANGKHAM, Phavone; PHIMPHISANE, Thavisay (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The purpose of the analysis of the impact of exchange rates on macroeconomic factors of Lao PDR from 2012-2022 aims to (1) analyze the fluctuation of macroeconomic factors and exchange rate of Kip/Dollar and Kip/Baht in the Lao PDR from 2012-2021 and (2) the impact of the exchange rate on the macroeconomic factors of the Lao PDR from 2012-2021. By bringing the collected data to summarize, interpret, consider, select and analyze by using descriptive statistical model and inferential statistics to find a value in percentage, parameter value of regression equation with OLS through E-view 12. The analysis results found that: the exchange rate of Kip/Dollar has effect on the Gross National Income (GNI) of the Lao PDR in the same direction relationship, if the exchange rate changes and increases, it means that the kip of Lao PDR is weak. The country will have the ability to compete in terms of price or make the income from exports that change the value of the kip increase and have a continuous effect on the wages of labor in businesses related to exports, investment and the purchasing power of consumers through income and the economic growth increases, lead to export and investment increase. That will result in the increase of the Gross National Income (GNI) of the Lao PDR. The Consumer Price Index of Lao PDR is continuously increasing, if the Dollar /Kip exchange rate increase by 1 US dollar (USD), it will cause the consumer price index (CPI) of Lao PDR to increase by 1.67% in US dollar (USD). For the exchange rate and export relationship of Lao PDR, it shows that if the exchange rate of Dollar/Kip increase by 1 US dollar (USD), it will result in the export value (EX) of Lao PDR increase by 11.15% US dollar (USD). In other side, the Thai/Kip Baht exchange rate is unable to explain the Gross National Income (GNI), Consumer Price Index (CPI) and Lao PDR's exports clearly, which means that there is no relationship among them, or in other words, the Thai Baht exchange rate does not affect the macroeconomic factors in the model of this research.